Visualization of heat transport using dimensionless heatfunction for natural convection and conduction in an enclosure with thick solid ceiling - Mobedi, Moghtada; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2008)
A conjugate conduction-(natural)convection problem is numerically studied in order to present the application of dimensionless heatfunction for entire computational domain including solid and fluid regions in an enclosure with thick solid ceiling. The modified dimensionless heatfunction for solid region is defined to provide continuity of dimensionless heatfunction on solid-fluid interface. The enclosure is differentially heated from vertical walls, and horizontal walls are adiabatic. Finite difference method is employed to solve the set of governing equations. The dimensionless governing parameters for computations are: Rayleigh number (from 103 to 106), dimensionless ceiling wall thickness (0.05 and 0.5) and thermal conductivity ratio(from 1 to 100). The obtained results shows that the heat and fluid flows in the enclosure are considerably influenced by Rayleigh number and thermal conductivity ratio. Dimensionless wall thickness comparatively has less effect on heat transfer rate through the cavity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Dimensionless heatfunction; Conjugate heat transfer; Natural convection; Heat transport; Heatline